"Modifiers" as Verbs: The Case of Mandarin1. (11th January 2018) - Lin, Tzong‐Hong Jonah; Yu, Jia‐Chi; Chen, Tzu‐Ling
Abstract: We show that some elements in Mandarin that have been considered as pre‐verbal adverbial modifiers are actually the main verbs of the sentences. Three sets of phenomena are discussed: the degree gou 'enough' construction, the "Adv/Adv‐ di " contrast, and two types of "manner wh ‐adverbs". These phenomena make Mandarin a typologically interesting case, as it stands in contrast to languages such as English on the one hand, where adverbs are adjuncts, and to Formosan languages on the other, where manner modifiers realize as the main verb of the sentence. We also discuss the possible parameterization in grammar that is responsible for this distinction. We suggest that grammatical theory provides an option to languages, in the form of a parameter, which licenses complementation of an un‐subcategorized expression YP to a head X, when X denotes a manner (or more generally, an event modifier) of YP.